2008
DOI: 10.2353/jmoldx.2008.070087
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Microsatellite Instability in Colorectal Cancer Using an Alternative Multiplex Assay of Quasi-Monomorphic Mononucleotide Markers

Abstract: Colorectal malignancies demonstrating microsatellite instability (MSI) have a very heterogeneous histological appearance, better prognosis, and altered response to therapy. Consequently, identification of the MSI phenotype is both relevant and interesting as a screening and prognostic tool and as a potential predictive factor of chemotherapeutic response. Several groups have argued for the exclusive use of mononucleotide markers for MSI analysis. In this study, an alternative MSI typing multiplex system of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“…Genomic instability clearly existed in the NTD samples, suggesting a defect in MMR function. Importantly, Bat25, Bat26, and Bat34C4 are located within intron-16 of the c-kit oncogene, intron-5 of the hMSH2, and the 3¢-untranslated region of exon-11 of P53, [26][27] respectively. D2S123 and D2S119 surround hMSH2 and hMLH1, whereas D3S1611 is located within hMLH1.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic instability clearly existed in the NTD samples, suggesting a defect in MMR function. Importantly, Bat25, Bat26, and Bat34C4 are located within intron-16 of the c-kit oncogene, intron-5 of the hMSH2, and the 3¢-untranslated region of exon-11 of P53, [26][27] respectively. D2S123 and D2S119 surround hMSH2 and hMLH1, whereas D3S1611 is located within hMLH1.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested using CAT25 in combination with BAT25 and BAT26 mononucleotide microsatellites. 14,21 The aim of this study was the characterization of the CAT25 mononucleotide marker and evaluation of its sensitivity and specificity in comparison with NCI Bethesda panel in colon cancer patients. The CAT25 allelic profile study, conducted in 100 healthy donor subjects, showed a (quasi) monomorphic allele pattern.…”
Section: Discussionmentioning
confidence: 99%
“…This method has substantial limitations, however, because of the inclusion of less sensitive and less specific dinucleotide markers (6,7 ). The current standard approach of MSI analysis is relatively time-consuming, laborious, and expensive, because allelic profiles between tumor and matching germlineand normal-tissue DNA must be compared (6,8 ). Recently the exclusive use of traditional (BAT25 and BAT26) and/or novel (CAT25, SEC63, NR-21, NR-22, NR-24, and NR-27) monomorphic mononucleotide repeat markers in various combinations has been successfully applied by some groups (6, 8 -13 ).…”
Section: © 2010 American Association For Clinical Chemistrymentioning
confidence: 99%